The emerging commuter families and changes in psychosocial and health behaviour profile - Ortega, Adriana; Abdullah, Haslinda; Roslan, Samsilah (Universiti Putra Malaysia Press, 2014)
The present paper provides a descriptive analysis of commuters and their families. It also explores gender differences and the impacts of commuting among young families in Malaysia. The study was conducted in the Klang Valley, and the sample consisted of commuters working outside the Klang Valley. Data were collected using in-depth interviews and a descriptive survey. The findings showed that 44.4% of commuters were working away from home because it was requested by their employers. Although there were more men than women who perceived the commuting lifestyle as a positive situation, there were not gender differences observed on how commuting impacted personal wellbeing. Nonetheless, significant differences were found between those with a positive outlook of the commuting life and those with a negative perception of the commuting lifestyle. The emerging commuter family dynamics and its impact on work-home life balance for young Malaysian families need to be further investigated.